Investigation of the effect of Arginine Silicate Inositol complex on the osseointegration level of titanium implants - Atas, Asime Gezer; Yildirim, Tuba Talo; Dundar, Serkan; Bozoglan, Alihan; Şahin, Kazım (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
Arginine silicate inositol complex is a material that increases bone mineral density and the amount of collagen in vascular tissue. The aim of this study was to investigate the effect of the Arginine silicate inositol complex, administered orally via gavage, on the osseointegration level of titanium implants in the tibiae of rats. The experimental animals were divided into four groups a control group, which had no implants or further treatment; a control-implant group, which had implants placed only in the tibia bone but no further treatment; an, Arginine silicate inositol-administered group, which had no implants but was administered Arginine silicate inositol; and an Arginine silicate inositol-implant group, which had both implants placed and Arginine silicate inositol administered. In serum samples obtained from the rats, associated with bone tissue; alkaline phosphatase, osteocalcin, calcium, phosphorus, associated with liver function; alanine aminotransferase, aspartate aminotransferase were analyzed using biochemical methods. Densitometric evaluations were performed on the jaw and femur bones. The titanium screws were removed along with the surrounding bone tissue for histological evaluation. Non Parametric Tests were used the data analysis: Mann-Whitney U (between two groups), Kruskal-Wallis and Dunn test (between four groups), bone-implant connection and thread fill levels did not show a statistically significant difference among the groups (P>0.05). The levels of calcium, alkaline phosphatase, osteocalcin, alanine aminotransferase, aspartate aminotransferase, femur bone mineral density and phosphorus also did not show a statistically significant difference among the groups (P>0.05). The differences in levels of jaw bone mineral density were statistically significant among the groups (P<0.05). Thus, it can be concluded that the Arginine silicate inositol complex may increase jaw bone mineral density, and bone-implant integration.
Investigación del efecto del complejo de silicato de arginina inositol en el nivel de oseointegración de implantes de titanio
Keywords: Arginine silicate inositol; slic one; arginine; osseointegration; bone implant connection